Hybridity and Christian identity - Jones, Arun W. (Missiology, 2022)
A hybrid identity, which results from an amalgamation of different cultures, different religious traditions and ideologies, and different social locations, with each having varying degrees of importance for identity formation, and being more or less well defined, has been a feature of Jewish and Christian life since biblical times. This article explores a variety of processes of hybridization in the formation of Christian identity. It also describes different effects that the condition of hybridity can have on Christian experience. Finally, it raises the question of whether hybridity should not be simply normal but also in some way normative in the religious self-understanding of Christians.